A rare case of popliteal pterygium syndrome - Mohamed Amine Oukhouya; Mohammed Tazi Charki; Hicham Abdellaoui; Karima Atarraf; Moulay Abderrahmane Afifi (Elsevier, 2023)
Popliteal pterygium syndrome is very rare genetic disorder, it can occur in multiple parts of the body, especially the kness with. This current case report describes a 14-day-old newborn admitted to the department of pediatric orthopaedic surgery for a popliteal pterygium syndrome. Clinical examination revealed an extensive bilateral popliteal webs. A doppler ultrasound was performed to specify the spatial relationship between the popliteal artery, the sciatic nerve, and the fibrous band. We proceeded to the resection of the webs with Z-plasties, and successive casts were performed.